KAJIAN ARSITEKTUR PERILAKU UNTUK RUANG LAKTASI DI RUANG PUBLIK - Yetti, Aprodita Emma (Universitas Aisyiyah Yogyakarta, 2018)
Breastfeeding is a positive activity that needs support from the surrounding environment. The lactation room is a necessary means of infrastructure to facilitate breastfeeding. The availability of adequate lactation space in public spaces is currently not maximized. This research is a qualitative descriptive research with case study approach. This research takes locus in public space that is urban shopping place. Methods of data collection using the technique of partial observation and behavior mapping. The results of this study can contribute to enrich the insight and knowledge in the field of education and practical use of referrals or referrals for the community, especially for the development of architectural.